ENGLISH EDUCATION STUDENTS’ PERCEPTION OF INSTAGRAM USAGE AS A MEDIUM TO LEARN ENGLISH - Anindita, Kezia; Noveintine, Dhanesvar Karel (Sanata Dharma University, Yogyakarta, 2022)
The popularity of Instagram made people increasingly use it well, one of which is to learn new languages. English as an international language is a language that is being encouraged to be mastered by people. The objective of this study is to know how EFL students use Instagram as an English learning medium. The data collected was from ELESP students’ batch 19-21 who learn English with Instagram as the learning medium. This study was conducted in a descriptive qualitative method by distributing an open-ended questionnaire. This study result showed that ELESP students have a positive perception of Instagram usage as the learning medium to learn English. ELESP students deliver how Instagram can enhance vocabulary, grammar, and pronunciation knowledge, and also gain new information.